Lesotho : Staff Report for the 2003 Article IV Consultation, Fifth Review Under the Poverty Reduction and Growth Facility, and Requests for Waiver of Performance Criteria and Extension of Arrangement. (IMF Staff Country Reports; Country Report, 2004)
Lesotho's economy has continued to perform well under the Poverty Reduction and Growth Facility (PRGF) arrangement despite adverse weather conditions and the regional food shortage. Executive Directors welcomed the strategy to achieve higher and sustainable economic growth, reduce poverty, and improve social conditions by creating private sector developments and labor-intensive industries. They appreciated the monetary and fiscal policies, the integration of PRGF objectives with the budget, and the improvement in the tax system. They emphasized the need to accelerate structural reforms and supported the Anti-Corruption Unit.